Reliability of Single Perforator Based Free Anterolateral Thigh Flap Reconstruction among Children with Post Traumatic Limb Defects - Shiza, Muhammad Aslam Khan, Waseem Humayoon, Hassan Saeed Khan, Ammar Ali Raza, Farhan Gohar, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To evaluate reliability of anterolateral thigh flap based on a single perforator in pediatric population for lower limb post traumatic defects. Study design: Retrospective cross sectional study Place and duration of study: Pediatric plastic surgery department of the children hospital & university of child health science, Lahore from January 2018 to January 2022. Methodology: After approval from ethical review board, 50 patients who underwent a free Alt flap reconstruction were included in this retrospective analysis. All flaps for lower limb post traumatic raised on a single perforator were included and reliability of flap was assessed for technical feasibility, outcomes and safety. Data was entered and analysed in SPSS ver: 21.0 and presented as frequency and percentages. Results: Mean age was 8.2±3.45 years 64% were males.96% had undergone road traffic accident (4% burn).Lower limb was affected in majority of patients 80% (upper limb 20%). 78% of patients were discharged at 10th post-operative day and 8% had partial flap loss. Conclusion: We concluded in this studyfree tissue transfer of anterolateral thigh flap based on a single perforator in children for covering large defects is a reliable method with good safety margin and minimal complication rate. Keywords: Anterolateral thigh flap, single perforator, pediatric population, free flap, free tissue transfer, perforator flap reliability